Comparison Of Foot Massage With Mixed Galangal Foot Soak Against Edema In The Feet Of Pregnant Women In The Third Trimester At The Nasywa Clinic - Rindy Arabella Margareta Andika; Lili Yuliana Tambunan; Paramita Mustari; Sri Junita Simaremare (Sean Institute, 2023)
Edema occurs in around 80% of pregnant women. There are several non-pharmacological interventions to reduce edema, namely foot massage and soaking in warm water mixed with galangal. Based on WHO data in 2020, pregnant women usually experience swelling in the second and third trimesters in the second trimester, namely 75%. If this edema is not treated quickly, it can be dangerous. Research Objective: to find out which foot massage or soaking in warm water mixed with Kaempferia galanga is more effective for pregnant women in the third trimester. Method: Quasy Experimental with a Two Group Pretest - Posttest Design. The population in this study was 40 people. The sample was divided into a control group of 20 people and an intervention group of 20 people using a sampling technique called total sampling. Data analysis used the t-dependent statistical test with a confidence level of 95%. Results: analysis of data obtained from the P-value shows no difference in the degree of foot edema in pregnant women who do foot massage and soak in warm water with a mixture of Kaempferia galanga. P-value = 0.814 (< 0.05) Conclusion: foot massage and soak in warm water The galangal mixture is equally effective in reducing edema in the legs of pregnant women in the third trimester.